Schöne Wissenschaften: Sammeln, Ordnen und Präsentieren im josephinischen Wien (2021)
"Schöne Wissenschaften" is dedicated to the art and natural science collections of the time of Emperor Joseph II (reigned 1765-1790). The Imperial Coin Cabinet, the Physical Cabinet and the Natural History Cabinet, the collection of wax anatomical models in the Josephinum and the Imperial Picture Gallery in the Upper Belvedere form the starting point for far-reaching questions on the history of the collections and the public and scientific understanding in Vienna during the Enlightenment. With "Schöne Wissenschaften" (Beautiful Sciences), a central philosophical term of the Enlightenment is taken up, in which different ideas of beauty and science are combined. These ideas played a role in art and natural science collections in the late 18th century and direct the attention to the revealing and interesting structures of knowledge and cognition of that time. Authors: Nora Fischer, Elisabeth Hassmann, Hans Christian Hönes, Eva Kernbauer, Markus Krajewski, Anna Mader-Kratky, Anna Maerker, Gernot Mayer, Debora J. Meijers, Christa Riedl-Dorn, Andrea Seidler, Werner Telesko und Thomas Wallnig...